Severe Hypocalcemia due to Denosumab in Metastatic Prostate Cancer - Mohammed Muqeet Adnan; Usman Bhutta; Tanzeel Iqbal; Sufyan AbdulMujeeb; Lukas Haragsim; Syed Amer (Case Reports in Nephrology)
Denosumab is a monoclonal antibody used for prevention of skeletal-related events (SREs) in patients with bone metastases from solid tumors. Hypocalcemia is a rare and dangerous side effect of the drug Denosumab. We present a case of a patient with metastatic prostate cancer who developed severe hypocalcemia after the administration of the drug. The patient’s vitamin D levels were low when checked after administration of the drug, which likely predisposed him to the development of hypocalcemia. He was placed on high doses of oral and intravenous (IV) calcium and vitamin D without any appreciable response in the serum calcium level. His ionized calcium remained below 0.71 mmol/L despite very high doses of oral and IV calcium supplements. During the hospital course, he developed hydronephrosis from the spread of a tumor and did not want to undergo percutaneous nephrostomy tube placement; therefore, it was decided to dialyse him for acute renal failure and to correct his hypocalcemia. Checking calcium and vitamin D levels prior to the administration of Denosumab is vital in preventing hypocalcemia. If hypocalcemia is severe and not responsive to high doses of vitamin D, oral and IV calcium, then hemodialysis with a high calcium bath can correct this electrolyte abnormality.